PERBANDINGAN BERBAGAI PANDANGAN DAN ALIRAN DALAM PENDIDIKAN MULTIKULTURAL - fitriana, Eli; Zubaedi; AlFauzan Amin; Hery Noer Ali (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
Multicultural education has evolved in response to the challenges of cultural diversity in the era of globalization. This article compares various perspectives and schools of thought within multicultural education, including traditional, critical, anti-racist, and postmodern approaches. Through a literature analysis, the study identifies differences in focus, strategies, and practical implications. The results indicate that the traditional approach emphasizes tolerance, while the critical school focuses more on issues of power and inequality. The conclusion suggests integrating these schools for a more inclusive education. Keywords : Multicultural education, educational schools, cultural diversity, tolerance, power.